Influência de práticas de gestão do conhecimento aplicadas ao desenvolvimento ágil de software - Candal, Diego Marconi (2022)
The demand for systemic integrations, software and innovative solutions has been growing at a fast pace today. Software development is an activity that uses knowledge as its main input, which makes software companies especially sensitive to this organizational asset. In the era of knowledge workers, it is understandable that there is an effort among software companies so that knowledge receives due attention, and it is desirable that these companies create mechanisms to work with knowledge, such as knowledge management practices. Agile software development, in turn, was consolidated among software companies through the implementation and application of methods and practices that follow the principles outlined in the 2001 agile manifesto. Within this context, this research aimed to identify the possible positive influence of the application of knowledge management practices in agile software development. Therefore, this exploratory-descriptive research with a qualitative approach carried out a literature review to establish the proposed theoretical model. The theoretical model refined and validated through a face/pilot test was applied in a controlled survey carried out using the Delphi method with academic experts and market professionals working on the topic addressed. As a result, it was possible to identify a consensus of 90.4% among the specialists participating in the research, thus validating the theoretical model. It is concluded that Knowledge Management practices can positively influence agile software development and its elements, facilitate activities, encourage the software development team to share their findings and that are relevant to companies and software teams, with the possibility of generating benefits when applied to the agile software development process of these companies and teams.